Actividades Áulicas de los estudiantes de octavo año de educación básica del Colegio Nacional Mixto Atahualpa de la ciudad de Machala provincia de El Oro. 2012. - Vera Delgado, Ana Ondina (2014)
Raised the hypothesis proceeded to conduct field research by applying a survey to students and teachers and an observation guide to perform a contrast information. The result of this research was processed and represented in statistical tables and charts with their analysis and interpretation.